TLC Fingerprint Analysis and Evaluation of α-Glucosidase Inhibitory and Free Radical Scavenging Activity of Justicia gendarussa from Different Growth Locations - Wulansari, Laela; Wahyuni, Wulan Tri; Nurcholis, Waras; Rafi, Mohamad (Department of Chemistry, Faculty of Science and Technology Syarif Hidayatullah Jakarta State Islamic University, 2025)
Justicia gendarussa is known to have antioxidant and antidiabetic properties, which are related to the composition and concentration of its metabolites and influenced by differences in growth location. This study aims to evaluate changes in metabolite profiles and biological activities, such as the inhibition of α-glucosidase and free radical scavenging in J. gendarussa genotypes from Bogor, Cianjur, and Sukabumi. Changes in metabolite profiles were assessed using thin-layer chromatography (TLC) fingerprint analysis combined with principal component analysis (PCA). Bioautography TLC using DPPH was performed to confirm the presence of antioxidant compounds. In the TLC fingerprint analysis of J. gendarussa, we obtained 14 bands with good resolution. PCA successfully grouped J. gendarussa extracts based on growth location. The percentage of α-glucosidase inhibitory and free radical scavenging activity was significantly different, with the highest percentage of inhibition of α-glucosidase shown by the IIIS genotype (99.23%) and the highest free radical scavenging (91.35%) demonstrated by the IIB genotype. The results of TLC bioautography confirmed the presence of antioxidant compounds in J. gendarussa represented by bands with Rf 0.04, 0.32, and 0.80. This study concludes that growth location differences influence the variations in metabolite profiles, α-glucosidase inhibitory activity, and free radical scavenging activity of J. gendarussa genotypes.